2021
DOI: 10.3390/cancers13040713
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Alterations in Triple-Negative Breast Cancer—The Critical Role of Extracellular Matrix

Abstract: Triple-negative breast cancer (TNBC) is an aggressive subgroup of breast cancer characterized by genomic complexity and therapeutic options limited to only standard chemotherapy. Although it has been suggested that stratifying TNBC patients by pathway-specific molecular alterations may predict benefit from specific therapeutic agents, application in routine clinical practice has not yet been established. There is a growing body of the literature supporting that epigenetic modifications comprised by DNA methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 98 publications
0
18
0
Order By: Relevance
“…This type of cell transformation is associated with chemical and morphological variations. Particularly regarding breast cancer (mainly TNBC), current data suggests that its initiation and progression may be associated to epigenetic alterations (such as DNA methylation or chromatin remodelling) [ 17 , 21 ]. Recent studies have focused on the biophysics of the cancer state, shedding a new light on carcinogenesis beyond the recognised biochemical and genetic variations associated to malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…This type of cell transformation is associated with chemical and morphological variations. Particularly regarding breast cancer (mainly TNBC), current data suggests that its initiation and progression may be associated to epigenetic alterations (such as DNA methylation or chromatin remodelling) [ 17 , 21 ]. Recent studies have focused on the biophysics of the cancer state, shedding a new light on carcinogenesis beyond the recognised biochemical and genetic variations associated to malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Here we report that the slight EGFR expression is correlated with a robust decrease in ERK1/2 phosphorylation in monoclonal shERb MDA-MB-231 cells, compared to the excessive phosphorylation in the invasive MDA-MB-231 cells. In previous studies, we have demonstrated that the distinct ER status of breast cancer cells is correlated to different microRNA (miRNA) epigenetic signatures and that specific miRNAs (i.e., miR-10b, miR-145 and miR-200b) are possible biomarkers for regulating breast cancer cell behavior by interacting with matrix mediators (19,20,53,54). Especially for ERb, this ER is the epigenetic mediator of miR-10b, miR-145 and miR-92, specific miRNAs implicated in breast cancer progression (19,55).…”
Section: Discussionmentioning
confidence: 99%
“…Negative control: isotype control HSPE, known to modulate these processes. 35,36 Gene expression was determined using qPCR.…”
Section: Syndecan-4 Silencing Leads To Alterations In the Gene Expression Of Adhesion Moleculesmentioning
confidence: 99%